A single feed dual-band (2.4 GHz/5 GHz) miniaturized patch antenna for wireless local area network (WLAN) communications. Issue 18 (11th December 2016) - Meng, Fanji; Sharma, Satish
Abstract: A single feed dual-band miniaturized microstrip patch antenna for Wireless Local Area Network (WLAN) communications has been proposed. The outer rectangular loop patch and inner modified E-shaped patch were used to resonate at 2.4 and 5 GHz, respectively. In order to separate the effect between two frequency bands, a shorting pin was set between two resonance cells. The simulated results show that it can operate at 2.4 and 5 GHz bands with 0.072 GHz (2.407–2.479 GHz) and 0.715 GHz (5.137–5.853 GHz) fractional bandwidth, respectively, which can cover the whole frequency band of WLAN. In addition, the antenna is miniaturized by 31% compared to the conventional rectangular patch without a slot. At last, the proposed microstrip patch antenna has been fabricated and measured for both impedance matching and radiation patterns. A comparison of the measurement and simulation results is given, which show reasonable good agreement.